Long time blood-transfusion trend in a European general hospital - Enko, Dietmar; Herrmann, Markus; Baranyi, Andreas; Schnedl, Wolfgang J.; Halwachs-Baumann, Gabriele (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Reports about long-time transfusion trends in Austrian hospitals are rare. In our hospital, we implemented an algorithm of preoperative anemia management as part of a patient blood management (PBM) program in October 2011. Anemic individuals with elective surgery underwent an adequate preoperative anemia classification and treatment with erythropoietin and intravenous iron. The aim of this study was to assess red blood cell (RBC), platelet and plasma transfusions before and after implementation of an anemia management program in a general hospital in Austria. This retrospective study evaluated a 12-year trend (2006 – 2017) of RBC, platelet and plasma transfusions in an Austrian general hospital comprising a 6-year period before (2006 – 2011) and a 6-year period after (2012 – 2017) the implementation of an algorithm-guided anemia management. From overall 49,142 transfused RBC units between 2006 - 2017, 22,745 units were transfused in the post-implementation period compared to 26,397 units before PBM initiation (-13.8 %). The plasma unit use decreased also distinctly (787 vs. 1065 units, - 26.1 %) in the period after PBM implementation, whereas a slight decrease of platelet concentration use (807 vs. 843 units, - 4.3 %) was observed, only. This study demonstrates a 12-year pattern of blood use in an Austrian hospital with a distinct decreasing trend of transfused RBC and plasma units during this period. The implementation of PBM activities decreased the need of blood utilization at our institution. Further initiatives are needed to continue this trend in the next years.
EXCLI Journal;Vol. 19 2020
Keywords: Anemia management; Blood transfusion; Transfusion practice; 610